'Counter-hegemonic networks and the transformation of global climate politics' by Jackie Smith: a response by Ronaldo Munck. Issue 2 (3rd July 2014) - Munck,
Abstract : This is a reply to:Smith, Jackie. 2014. "Counter-hegemonic networks and the transformation of global climate politics: rethinking movement-state relations." Global Discourse . 4 (2–3): 120–138. http://dx.doi.org/10.1080/23269995.2013.874111